2018
DOI: 10.1038/s41598-018-26784-9
|View full text |Cite
|
Sign up to set email alerts
|

Basal interferon signaling and therapeutic use of interferons in controlling rotavirus infection in human intestinal cells and organoids

Abstract: Rotavirus (RV) primarily infects enterocytes and results in severe diarrhea, particularly in children. It is known that the host immune responses determine the outcome of viral infections. Following infections, interferons (IFNs) are produced as the first and the main anti-viral cytokines to combat the virus. Here we showed that RV predominantly induced type III IFNs (IFN-λ1), and to a less extent, type I IFNs (IFN-α and IFN-β) in human intestinal cells. However, it did not produce detectable IFN proteins and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 54 publications
2
24
2
Order By: Relevance
“…Our results showed that IFN-γ decreases in the positive samples of rotavirus in contrast to the negative samples, which is mainly due to the developed mechanisms established by many viruses to confront the innate immunity, in order to replicate efficiently inside the cell without any restriction by the body defenses, such as IFNs. In line with our finding, Hakim et al [29] , who conducted his study in murine models using IFN-I (α, β) and IFN-II (γ) as a therapy against rotavirus, failed in defense and giving resistance against the invaded rotavirus. These results proved that IFN-I and -II have a secondary role in controlling rotavirus infection in mice and also suggested that IFN-III (IFN-λ) is advantageous in mice models and is inhibited by the virus in intestinal epithelial cells [29][30][31] , which gives a better resistance against rotavirus.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed that IFN-γ decreases in the positive samples of rotavirus in contrast to the negative samples, which is mainly due to the developed mechanisms established by many viruses to confront the innate immunity, in order to replicate efficiently inside the cell without any restriction by the body defenses, such as IFNs. In line with our finding, Hakim et al [29] , who conducted his study in murine models using IFN-I (α, β) and IFN-II (γ) as a therapy against rotavirus, failed in defense and giving resistance against the invaded rotavirus. These results proved that IFN-I and -II have a secondary role in controlling rotavirus infection in mice and also suggested that IFN-III (IFN-λ) is advantageous in mice models and is inhibited by the virus in intestinal epithelial cells [29][30][31] , which gives a better resistance against rotavirus.…”
Section: Discussionsupporting
confidence: 91%
“…In line with our finding, Hakim et al [29] , who conducted his study in murine models using IFN-I (α, β) and IFN-II (γ) as a therapy against rotavirus, failed in defense and giving resistance against the invaded rotavirus. These results proved that IFN-I and -II have a secondary role in controlling rotavirus infection in mice and also suggested that IFN-III (IFN-λ) is advantageous in mice models and is inhibited by the virus in intestinal epithelial cells [29][30][31] , which gives a better resistance against rotavirus. It has also been revealed that the gene expression of IFNs is down-regulated by rotavirus infection [32] ; a rotavirus developed mechanism impedes STAT-Y701 phosphorylation with IFN overexpression [33] .…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies used human intestinal enteroid (HIE) cultures as a mini-gut model to study human RVs (38,(47)(48)(49)(50)(51)(52). HIEs contain multiple epithelial cell types and possess complexity and cell diversity comparable with that of the intestinal epithelium.…”
Section: Fig 4 Legend (Continued)mentioning
confidence: 99%
“…In humans, epithelial cells within the lung, intestine and liver among others, are uniquely IFN-λ sensitive. In particular, IFN-λs have been shown to protect against pulmonary influenza and human metapneumovirus (HMPV) (7, 8), gastrointestinal rotavirus and norovirus (9, 10) and hepatic HBV and HCV (11, 12). While the majority of human studies have been performed in vitro , murine studies have shown potent antiviral effects of IFN-λs against numerous viruses including influenza and SARS coronavirus (13, 14), rotavirus, norovirus, and reovirus (1517).…”
Section: Introductionmentioning
confidence: 99%